Litter as a marker of anthropotechnogenic changes in the pine forests in the plain part of Ukraine - Ворон, В. П.; Коваль, І. М. (Forestry and Forest Melioration, 2024)
Introduction Rational forest use should be based on a comprehensive investigation of the mechanisms of the environmental factors that influence forest stands. The severity of the destructive process in the forest litter depends on precipitation and litter decomposition activity. Under certain conditions, the thickness and structure of forest litter may contribute to fire emergence. As litter is the main component of combustible materials in the forest ecosystem, its mass and condition may determine fire development. The research aimed to reveal the features of changes in the precipitation-litter link in pine forests under anthropogenic influence. Materials and Methods The study of the forest litter formation under aerotechnogenic pollution was carried out on permanent sample plots in the industrial zones: Rivne Industrial Joint Stock Company “Azot” (RVAT “Azot”) and Lysychansk-Rubizhne-Siverodonetsk Industrial Agglomeration with dominance in emissions of SO2, NOx, NH3 and Zmiiv Thermal Power Plant, the emissions of which are dominated by oxides of sulfur, nitrogen and ash with a high content of heavy metals. The floor and litter stocks were assessed in the pine forests in the green zone of Kharkiv, in the ecological series of sample plots according to the stages of recreational digressions. Results Under industrial pollution, markers of change in the forest litter are associated with the chemical influence of pollutants. The content of pollutants increases from the top to the bottom layer of litter. These trends are particularly pronounced for heavy metals. The total stock of heavy metals in the litter in the industrial zone was 3.4–5.5 times higher than in the control area. As a result of pollution, the litter mass increases, so the rate of phytodetritus mineralization is an important indicator of technogenic influence. It was found that the total time for the formation of the mortmass in the industrial zone was 0.9–3.0 years longer than in the control plot. Changes in forest litter under recreational influence are associated with mechanical pressure. As a result of the recreational load, the slow biocycle in the precipitation-litter chain, which is typical for pine forests, is further inhibited. In all layers of litter mineralization, the accumulation of mortmass dominates over decomposition. Conclusions The total time of forest floor formation was 0.9–3.0 years longer in the industrial zone than in the control zone. The content of pollutants, in particular S and N, increased from the upper to the lower litter layer. The Cr content in the H layer of the litter was 12–14 times higher than in the L layer, Cu content was 4–19 times higher, Zn content – 7–11 times, Sr content – 8–13 times, Pb content – 13–18 times. In general, the stock of heavy metals in the litter in the industrial zone was 3.4–5.5 times higher than in undisturbed forests. Pine stands in relatively poor forest site conditions accumulate higher litter stocks than in poor site conditions: in 60-year-old stands, it was 35,500 kg ha-1 in relatively poor site conditions and 70,300 kg ha-1in poor site conditions. 9 Tables, 20 Refs.